Observations of Magnetic Flux Ropes Opened or Disconnected From the Sun by Magnetic Reconnection in Interplanetary Space - Feng, Hengqiang; Zhao, Yan; Wang, Jiemin; Liu, Qiang; Zhao, Guoqing (Frontiers in Physics, 2021)
During solar eruptions, many closed magnetic flux ropes are ejected into interplanetary space, which result in a continuous increase in the magnitude of the heliospheric magnetic field. However, the magnitude does not increase continuously, which indicates that there must be some mechanism for losing magnetic field magnitude. To discover the reason for this decrease, we examined all the magnetic and plasma data measured in 1997 by the Wind spacecraft and identified 621 reconnection exhausts. Of the 621 reconnection events, 31 were observed at the boundaries of magnetic flux ropes and were found to be opening or disconnecting magnetic field lines to the adjacent ropes. Of the 31 magnetic reconnection events, 29 were interchange reconnections, and the closed field lines of these related flux ropes were opened by them. Only 2 of the 31 magnetic reconnection events were disconnecting the opened field lines of the original flux ropes. These observations indicate that the interplanetary magnetic reconnections near the boundaries of flux ropes make important contributions towards balancing the increased magnetic field magnitude. However, this does not mean that magnetic reconnections near the Sun do not affect the balance of the magnetic magnitude in the heliosphere. As long as magnetic reconnections are near the flux ropes, they can contribute to balancing the increased magnetic field magnitude, regardless of the distance from the Sun.